Simultaneous three-dimensional temperature and velocity field measurements using astigmatic imaging of non-encapsulated thermo-liquid crystal (TLC) particles. Issue 3 (28th November 2014) - Segura, Rodrigo; Rossi, Massimiliano; Cierpka, Christian; Kähler, Christian J.
Abstract : TLC thermography and APTV for simultaneous time-resolved 3D temperature and velocity measurements in microflows. Abstract : A combination of cutting edge developments is presented to characterize three-dimensional (3D) temperature and velocity fields in microscopic flows. An emulsion of non-encapsulated thermo-liquid crystal (TLC) micro spheres, with a narrow size distribution is used to track the flow's motion and temperature distribution. A state-of-the-art light engine, which combines the spectrum of six light pipes, provides a balanced illumination which allows for strong and detectable color patterns across the TLC's temperature response range. Lastly, the ability of the TLC material to reflect select wavelength bands with an unchanging and independent circular polarization chirality is exploited by a filter that blocks background noise, while exclusively transmitting the color signal of the TLC particles. This approach takes advantage of the peculiar physical properties of TLCs to allow the estimation of individual TLC particle's 3D position, for the first time, using Astigmatism Particle Tracking Velocimetry (APTV).